Theoretical perspective for the relationship between molecular structures and circularly polarised thermally activated delayed fluorescence properties. (2nd November 2022) - Liu, Shulei; Qin, Ming; Liu, Songsong; Gao, Yang; Li, Bihe; Lin, Lili; Wang, Chuan-Kui; Fan, Jianzhong; Song, Yuzhi
Abstract : Circularly polarised thermally activated delayed fluorescence (CP-TADF) molecules producing circularly polarised light which is beneficial to human eyes are widely used in circularly polarised organic light-emitting diodes. However, the relationship between the molecular structures and their luminescence properties of these CP-TADF molecules has not been well explained. Herein, the chiral molecule (R)-SFST with properties of circularly polarised luminescence (CPL) and thermally activated delayed fluorescence (TADF) is studied in detail. Firstly, we found two conformations by using molecular dynamic conformation search for (R)-SFST, namely (R)-SFST-a and (R)-SFST-b. The molecular geometric structures of singlet and triplet states are optimised by utilising density functional theory (DFT) and time-dependent density functional theory (TD-DFT) methods. Combining the thermal vibration correlation function methods, their photophysical properties are studied simultaneously. The processes of excited-state energy decay are revealed. The results show that the chiral units are more important to the molecular orbitals when the molecule has a more distorted configuration, which is beneficial to obtain CPL properties. However, when the molecular has rigid configuration, the excitons are easier to convert between S1 and T1, and the molecular has better TADF properties. Our results reveal the influence of different molecular conformations on CPL and TADF properties. GRAPHICAL ABSTRACT: UF0001